A NEW RECORD OF CALAXIUS ACUTIROSTRIS (SAKAI AND de SAINT LAURENT, 1989) (FAMILY: AXIIDAE: BOR- RADAILE, 1903) (CRUSTACEA: DECAPODA: AXIIDEA) OFF THOOTHUKUDI, SOUTHEAST COAST OF INDIA (08º 53.6’N 78º 16’E and 08º 53.8’N 78º 32’E) - T. Vaitheeswaran; T. Rajasekaran; S. Balasubramani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A new record of Axiidae off Thoothukudi coast of Gulf of Mannar, southeast coast of India is reported. Calaxius acutirostris species is newly recorded from Indian waters. The present species (Calaxius acutirostris) are recorded from Thoothukudi coast of Gulf of Man- nar, southeast coast of India. One specimen was caught at the depth of 310 m as an incidental by-catch. It was found in tropical waters from about 08º 53.6’N 78º 16’E and 08º 53.8’N 78º 32’E/310m from Thoothukudi fishing harbour, southeast coast of India.